Pengaruh terapi wudhu dan murottal Al-Qur’an terhadap kecemasan siswa dalam menghadapi ujian - Yunitasari, Eva; Aliun, Fatimah Wahab; Oktarosada, Dwi (JOURNAL OF Public Health Concerns, 2025)
Background: Anxiety is an emotional response to an individual's perspective that is subjective and has no known cause. The global prevalence of anxiety in the world is 3.6 Psychological problems that are often experienced by students, namely fear of failure, getting bad grades and not being able to do exams, are included in their own burdens that cause levels of anxiety. Action or therapy is needed to minimize the incidence of anxiety. Non-pharmacological therapy as an alternative and solution, including hydrotherapy therapy, namely ablution techniques and also murottal Al-Qur'an. Purpose: To identify the effect of ablution and murottal Al-Qur'an on changes in students' anxiety in facing exams. Method: Pre-experimental research with one group design, pre-test and post-test design. The population in this study were all students of class XII of Al Ihya Islamic Boarding School Kalirejo Lampung Tengah in the 2022/2023 academic year, totaling 110 people consisting of 3 classes. Using random sampling technique, 30 students were selected as respondents. The intervention variables in this study were ablution therapy and Al-Quran recitation, while the dependent variable was anxiety. The instrument used in this study was the Visual Analog Scale for Anxiety (VAS-A). Data were processed using statistical tests using paired T-tests. Results: The level of anxiety of respondents before ablution and murottal Al-Qur'an therapy was in the range of 12-41 and after ablution and murottal Al-Qur'an therapy was in the range of 8-28. While the average value of the level of anxiety of respondents before ablution and murottal Al-Qur'an therapy was at a score of 30.83 and after ablution and murottal Al-Qur'an therapy was at a score of 17.80. For the standard deviation value of the level of anxiety of respondents before ablution and murottal Al-Qur'an therapy was at a score of 6.41 and after ablution and murottal Al-Qur'an therapy was at a score of 5.77. Based on the normality test, the value of the level of anxiety of respondents before ablution and murottal Al-Qur'an therapy was 0.117 and after ablution and murottal Al-Qur'an therapy was 0.247. Meanwhile, based on the T-paired test between the level of anxiety of respondents before and after ablution therapy and Al-Qur'an recitation, the value was 13.03 and p-value = 0.001. Conclusion: Ablution therapy and Al-Quran recitation have a significant effect in reducing students' anxiety levels in facing exams. Providing ablution therapy and Al-Quran recitation to reduce anxiety is very effective when done in a duration of 15-30 minutes and can be done at any time to control anxiety.   Suggestion: As an alternative solution, schools or educational institutions can implement ablution therapy and listen to the recitation of the Al-Quran to control the mental state of students who experience anxiety. Keywords: Ablution therapy; Al-Quran recitation; Anxiety Pendahuluan: Kecemasan merupakan respon emosional terhadap perspektif individu yang bersifat subjektif dan tidak diketahui penyebabnya. Prevalensi global kejadian kecemasan di dunia adalah sebanyak 3.6 Masalah psikologis yang sering dialami siswa yaitu takut gagal, mendapat nilai jelek dan tidak bisa mengerjakan ujian adalah termasuk beban tersendiri yang menimbulkan tingkat rasa kecemasan. Tindakan atau terapi sangat diperlukan untuk meminimalkan kejadian kecemasan. Terapi nonfarmakologis sebagai alternatif dan solusi, diantaranya  dengan terapi hidroterapi yaitu teknik wudhu dan juga murottal Al-Qur’an. Tujuan: Untuk mengidentifikasi pengaruh wudhu dan murottal Al-Qur’an terhadap perubahan kecemasan siswa/siswi dalam menghadapi ujian. Metode: Penelitian pre-eksperimen dengan rancangan one group design, pre-test dan post-test design. Populasi pada penelitian ini adalah seluruh siswa/siswi kelas XII pondok pesantren Al  Ihya Kalirejo Lampung Tengah tahun ajar 2022/2023 sebanyak 110 orang yang terdiri dari  3 kelas. Dengan teknik random sampling mendapatkan sebanyak 30 siswa/siswi untuk menjadi responden. Variabel intervensi dalam penelitian ini yaitu terapi wudhu dan murottal Al-Qur’an, sedangkan variabel dependennya yaitu kecemasan. Instrumen yang digunakan dalam penelitian ini adalah Visual Analog Scale for Anxiety (VAS-A). Data diolah dengan Uji statistik menggunakan T-test berpasangan atau paired T test. Hasil: Tingkat kecemasan responden sebelum terapi wudhu dan murottal Al-Qur’an dalam rentang skor 12-41 dan sesudah terapi wudhu dan murottal Al-Qur’an dalam rentang skor 8-28. Sedangkan nilai rata-rata tingkat kecemasan responden sebelum terapi wudhu dan murottal Al-Qur’an berada di skor 30.83 dan sesudah terapi wudhu dan murottal Al-Qur’an berada di skor 17.80.  Untuk nilai standar deviasi tingkat kecemasan responden sebelum terapi wudhu dan murottal Al-Qur’an berada di skor 6.41 dan sesudah terapi wudhu dan murottal Al-Qur’an berada di skor 5.77. Berdasarkan uji normalitas mendapatkan nilai tingkat kecemasan responden sebelum terapi wudhu dan murottal Al-Qur’an sebesar 0.117 dan sesudah terapi wudhu dan murottal Al-Qur’an sebesar 0.247.  Sedangkan berdasarkan uji T-paired test antara tingkat kecemasan responden sebelum terhadap sesudah terapi wudhu dan murottal Al-Qur’an mendapatkan nilai 13.03 dan p-value=0.001. Simpulan: Terapi wudhu dan murottal Al-Qur’an memberikan pengaruh yang signifikan dalam menurunkan tingkat kecemasan siswa/siswi dalam menghadapi ujian. Pemberian terapi wudhu dan murottal Al-Qur’an untuk menurunkan kecemasan sangat efektif di lakukan dalam durasi 15 – 30 menit dan dapat dilakukan kapanpun untuk mengendalikan rasa kecemasan. Saran: Sebagai solusi alternatif pada pihak sekolah atau lembaga pendidikan dapat menerapkan terapi wudhu dan mendengarkan murottal Al-Qur’an untuk mengendalikan mental siswa/siswi yang mengalami kecemasan